2018
DOI: 10.2147/jpr.s158737
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine attenuates persistent postsurgical pain by upregulating K<sup>+</sup>&ndash;Cl<sup>&minus;</sup>&nbsp;cotransporter-2 in the spinal dorsal horn in rats

Abstract: BackgroundDexmedetomidine (DEX) could have an analgesic effect on pain transmission through the modulation of brain-derived neurotrophic factor (BDNF). In addition, KCC2-induced shift in neuronal Cl− homeostasis is crucial for postsynaptic inhibition mediated by GABAA receptors. Accumulating evidence shows that nerve injury, peripheral inflammation and stress activate the spinal BDNF/TrkB signal, which results in the downregulation of KCC2 transport and expression, eventually leads to GAGAergic disinhibition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…KCC2 upregulation was also reported after SCI and administration of corticosteroids (Dai et al, 2018). The reactive microglia -BDNF -TrkB signaling was shown to be a main actor for KCC2 downregulation (Coull et al, 2005;Ferrini and De Koninck, 2013;Rivera, 2004;Rivera et al, 2002). In accordance with this, we have previously shown that the administration of a TrkB receptor antagonist after UVN increases KCC2 expression (Dutheil et al, 2016).…”
Section: Acute Anti-inflammatory Treatment Alters Adaptive Post-lesiosupporting
confidence: 68%
See 2 more Smart Citations
“…KCC2 upregulation was also reported after SCI and administration of corticosteroids (Dai et al, 2018). The reactive microglia -BDNF -TrkB signaling was shown to be a main actor for KCC2 downregulation (Coull et al, 2005;Ferrini and De Koninck, 2013;Rivera, 2004;Rivera et al, 2002). In accordance with this, we have previously shown that the administration of a TrkB receptor antagonist after UVN increases KCC2 expression (Dutheil et al, 2016).…”
Section: Acute Anti-inflammatory Treatment Alters Adaptive Post-lesiosupporting
confidence: 68%
“…Their inhibition after acute anti-inflammatory treatment is associated with altered vestibular compensation, probably highlighting their contribution to functional recovery. Glial reactions are crucial for adaptative post-lesional plasticity mechanisms in the VNs, since they promote preservation of tissue integrity and wound repair (Cherry et al, 2014;Myer, 2006;Quintana, 2017) and modulate neuronal network excitability through various mechanisms such as K + clearance (Bellot-Saez et al, 2017) and Brain-Derived-Neurotrophic-Factor (BDNF) signaling (Coull et al, 2005;Ferrini and De Koninck, 2013).…”
Section: Acute Anti-inflammatory Treatment Alters Adaptive Post-lesiomentioning
confidence: 99%
See 1 more Smart Citation
“…If operating for neuroma, we have the patient mark their point of maximum tenderness and any trigger points with a permanent marker. After undergoing the induction of general anesthesia, patients receive a pre-operative IV regional block (Bier) with lidocaine and dexmedetomidine [85][86][87][88]. If this is not possible because we are not operating on a limb amenable to tourniquet application, a pre-operative proximal nerve block or epidural is performed.…”
Section: Peri-operative Carementioning
confidence: 99%
“…However, in chronic pain conditions, there may be spontaneous pain, as well as intermittent pain, which is induced by persistent inflammation from structural damage or functional degeneration. Chronic pain is also associated with complex changes in peripheral and central signal processing [24].…”
Section: Treatment Of Pain Based On Anti-inflammation and Regenerationmentioning
confidence: 99%